2023
DOI: 10.3389/fendo.2023.1220426
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 21 in metabolic syndrome

Abstract: Metabolic syndrome is a complex metabolic disorder that often clinically manifests as obesity, insulin resistance/diabetes, hyperlipidemia, and hypertension. With the development of social and economic systems, the incidence of metabolic syndrome is increasing, bringing a heavy medical burden. However, there is still a lack of effective prevention and treatment strategies. Fibroblast growth factor 21 (FGF21) is a member of the human FGF superfamily and is a key protein involved in the maintenance of metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 120 publications
1
8
0
1
Order By: Relevance
“…There is evidence to indicate the promising potential of FGF21 administration in addressing cardiometabolic disorders, such as obesity, diabetes and ageing ( 5 , 6 , 8 , 31 ). Herein, significantly elevated serum levels of FGF21 were observed in rats post-infarction, consistent with previous reports that serum FGF21 levels paradoxically increase in diabetes and its cardiovascular complications ( 9 , 32 ). Hence, the increased serum levels of FGF21 and the decreased expression of KLB following MI may reflect a compensatory response to FGF21 resistance ( 5 ).…”
Section: Discussionsupporting
confidence: 92%
“…There is evidence to indicate the promising potential of FGF21 administration in addressing cardiometabolic disorders, such as obesity, diabetes and ageing ( 5 , 6 , 8 , 31 ). Herein, significantly elevated serum levels of FGF21 were observed in rats post-infarction, consistent with previous reports that serum FGF21 levels paradoxically increase in diabetes and its cardiovascular complications ( 9 , 32 ). Hence, the increased serum levels of FGF21 and the decreased expression of KLB following MI may reflect a compensatory response to FGF21 resistance ( 5 ).…”
Section: Discussionsupporting
confidence: 92%
“…High levels of circulating FGF21 are often linked to different dysfunctional metabolic processes, such as obesity [ 36 ]. In accordance with these studies, we found an upregulation of this hormone in the serum of the obese group, suggesting that serum FGF21 levels are indicative of a lipid dysregulation that occurs in obese patients with MAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of circulating FGF21 are observed in various metabolic disorders, including DM, obesity, and cardiovascular disease. This seemingly paradoxical occurrence is commonly characterized as a state of "FGF21 resistance" or viewed as a compensatory protective response to metabolic stress (36,37). A clinical investigation assessed circulating FGF21 levels in 2066 hospitalized patients with DM, revealing that individuals in the low urinary glucose excretion group exhibited higher body mass index (BMI) and serum FGF21 levels.…”
Section: Energy Metabolism and Innate Immunity In Dkdmentioning
confidence: 99%